PRASANGKA APA YANG PERLU DIBONGKAR DALAM DIALOG ANTAR UMAT BERAGAMA? - Bonifatius Haryo Wicaksono (Litbang STFT Widya Sasana Malang, 2015)
The differentiation of religions might constitute some prejudices to other religions. Prejudices that arise can make a fault if those are not processed properly. Prejudices are very dangerous if they are used to falsify other religious communities. Prejudices must require many ways to be clearly understood. For that, people should be aware of things that might be considered as prejudices. Inter-religious dialogue today has become a necessity in many multireligious countries. Without inter-religious dialogue, we do not know how far an inter-religious encounter can lead to positive or negative things. Encounter in inter-religious dialogue is a way to remove these prejudices. It takes a process that is not brief to open the differentiation of religions. However, through that many processes, every person learns to find what is good in others and himself. Efforts to deepen the faith and to learn from other religious communities are steps and can proceed to remove the prejudices